2021
DOI: 10.3390/ma14112806
|View full text |Cite
|
Sign up to set email alerts
|

Developments for Collagen Hydrolysate in Biological, Biochemical, and Biomedical Domains: A Comprehensive Review

Abstract: The collagen hydrolysate, a proteinic biopeptide, is used for various key functionalities in humans and animals. Numerous reviews explained either individually or a few of following aspects: types, processes, properties, and applications. In the recent developments, various biological, biochemical, and biomedical functionalities are achieved in five aspects: process, type, species, disease, receptors. The receptors are rarely addressed in the past which are an essential stimulus to activate various biomedical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 172 publications
(353 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have demonstrated that oral intake of enzymatically hydrolyzed collagen peptides can have positive effects on skin health, such as dermal ECM generation, fibroblast growth, antioxidation, recovery, elasticity, and wrinkle reduction [6][7][8][9][10] . Particularly, gelatin-and collagenoriented hydrolysates are widely applied these days and produced in a variety of fields, such as the fields of functional foods, nutraceuticals, medical supplies, and the biotech industry [11][12][13] . The molecular weight of gelatin, a water-soluble polymer, is considerably higher than that of collagen hydrolysates, and it is produced by enzymatically hydrolyzing collagen that is normally used as a food ingredient and delivery carrier for the regulated distribution of bioactivities [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that oral intake of enzymatically hydrolyzed collagen peptides can have positive effects on skin health, such as dermal ECM generation, fibroblast growth, antioxidation, recovery, elasticity, and wrinkle reduction [6][7][8][9][10] . Particularly, gelatin-and collagenoriented hydrolysates are widely applied these days and produced in a variety of fields, such as the fields of functional foods, nutraceuticals, medical supplies, and the biotech industry [11][12][13] . The molecular weight of gelatin, a water-soluble polymer, is considerably higher than that of collagen hydrolysates, and it is produced by enzymatically hydrolyzing collagen that is normally used as a food ingredient and delivery carrier for the regulated distribution of bioactivities [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight of gelatin, a water-soluble polymer, is considerably higher than that of collagen hydrolysates, and it is produced by enzymatically hydrolyzing collagen that is normally used as a food ingredient and delivery carrier for the regulated distribution of bioactivities [14][15][16][17] . When the high molecular weight of gelatin is hydrolyzed by treating a particular fungal or bacterial protease, the outputs, small molecular weight peptides, are conveniently called collagen hydrolysate 11,12,18 . There is growing evidence indicating that collagen peptides improve not only human skin indicators associated with aging, such as hydration, wrinkles, and elasticity, but also the antihypertensive effect in spontaneously hypertensive rats (SHRs) 19 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interest in inner beauty foods is increasing to maintain healthy skin, and research has been actively conducted to identify ingredients for inner beauty foods. Peptides derived from protein hydrolysis, particularly collagen hydrolysis, have been used as potential molecules for wrinkle improvement, moisturization and increased elasticity and analyzed for specific skin effects (1,2).…”
Section: Introductionmentioning
confidence: 99%